Motivational systems of college student leaders and non-leaders - Guillermo, Virginia D. 1927- (1972)
This study investigates how the leadership measures compare among the leaders and non-leaders, how the motivational profile of the student leader compare with that of a non-leader, how these motivational dimensions are related, and how these dimensions are related in terms of sex and economic status.
Thesis (D.Ed.)--University of the Philippines, Diliman.
Keywords: Students -- Philippines; Leadership; Student activities